“Get the best out of what comes in” – adaptation of the microbiota of chamois (Rupicapra rupicapra) to seasonal forage availability in the Bavarian Alps - Dahl, Sarah-Alica; Seifert, Jana; Camarinha-Silva, Amélia; Hernández-Arriaga, Angélica; Windisch, Wilhelm; König, Andreas (Frontiers in Microbiology, 2023)
As an inhabitant of the Alps, chamois are exposed to significant climatic changes throughout the year and are also strongly confronted with changing forage availability. Besides horizontal and vertical migratory movements as an adaptation, it undergoes physiological transformations and dynamic changes in the ruminal microbiota. The following study used 48 chamois of different ages and sexes to investigate to which extent the ingested food plants, the resulting crude nutrients in the rumen (reticulorumen) contents, and the bacterial microbiota in the rumen and their fermentation products were influenced by the changes over the seasons. Very little is known about the microbiota of wild ruminants, and many bacterial taxa could only be determined to certain taxonomic levels in this study. However, adapted microbiota reflects the significant changes in the ingested forage and the resulting crude nutrients. For some taxa, our results indicated potential functional relationships. In addition, 15 genera were identified, representing almost 90% of the relative abundance, forming the central part of the microbial community throughout the year. The successful and flexible adaptation of chamois is reflected in the chamois rumen's nutrient and microbial profile. This is also the first study that analyzes the microbiota of the chamois using rumen samples and considers the microbiota in a seasonal comparison.